Capecitabine-induced coronary artery vasospasm in a patient who previously experienced a similar episode with fluorouracil therapy - Uğur Nadir Karakulak; Elifcan Aladağ; Naresh Maharjan; Kenan Övünç (KARE Publishing, 2016)
Capecitabine is a chemotherapeutic agent used in the treatment of metastatic colon cancer and metastatic breast cancer. It is metabolized into fluorouracil (5-FU) in the liver; hence, its mechanism of action is similar to that of 5-FU. Cardiac toxicity, although rarely seen, may be of concern in some patients. Although multiple hypotheses have been proposed for the mechanism of cardiotoxicity, coronary vasospasm is the most commonly accepted one, as patients usually present with chest pain resembling acute myocardial infarction. Electrocardiography may demonstrate ST-segment elevation, and cardiac biomarkers may be elevated. Cardiotoxicity with 5-FU has been reported widely. Capecitabine has been shown to be much less cardiotoxic compared to 5-FU, with only a handful of cases reporting cardiotoxicity with capecitabine. There are no cases reporting cardiotoxicity with both 5-FU and capecitabine in the same patient. In this case report, we present a patient with adverse cardiac effect with capecitabine whose previous 5-FU therapy was stopped due to cardiotoxicity.